A Model for Determining Optimal Profit Sharing Plans - von Lanzenauer, Christoph Haehling (Journal of Financial and Quantitative Analysis, 1969)
The concept of profit sharing—whereby a company provides employees with a contribution above and beyond their regular wages based upon business profits—is very old indeed. Implementation of this concept is witnessed by the many profit sharing plans of all kinds in existence today. However, even though the concept is old and the use widespread, there is a complete void in published literature on the nature of optimal profit sharing plans. It is the purpose of this paper to investigate this subject.